Echinococcus granulosus sensu lato promotes osteoclast differentiation through DUSP4-MAPK signaling in osseous echinococcosis - Sun, Haohao; Liu, Yaqing; Huang, Yiping; Xiong, Kangjun; Zhang, Zhendong; Wang, Weishan; Dai, Yi; Li, Jing; Li, Qi; Wang, Sibo; Shi, Chenhui (Frontiers in Microbiology, 2025)
IntroductionOsseous echinococcosis, caused by Echinococcus granulosus infection, is characterized by progressive bone destruction driven by abnormal osteoclast activation. Dual-specificity phosphatase 4 (DUSP4), a key negative regulator of the MAPK pathway, inhibits osteoclast differentiation and bone resorption. This study aimed to elucidate the role of DUSP4 in E. granulosus-induced bone loss.MethodsIn vitro, a co-culture system of E. granulosus protoscoleces (PSCs) and bone marrow-derived macrophages (BMMs) was established. Osteoclast differentiation and bone resorption were assessed using TRAP staining and F-actin immunofluorescence. Transcriptome sequencing identified DUSP4 as a key regulator. DUSP4 overexpression was performed to evaluate its effects on osteoclast markers and MAPK signaling (ERK, JNK, p38). In vivo, a mouse model of osseous echinococcosis was developed, and DUSP4 overexpression was achieved via lentiviral transduction. Bone destruction was analyzed using X-ray, micro-CT, and histology.ResultsPSCs significantly enhanced osteoclast differentiation and bone resorption, upregulated osteoclast markers (CTSK, NFATc1), and activated MAPK signaling. DUSP4 overexpression reversed these effects, reducing osteoclast activity and MAPK phosphorylation. In vivo, PSC infection caused severe bone destruction, which was mitigated by DUSP4 overexpression.DisscussionThis study reveals the molecular mechanism by which Echinococcus granulosus drives abnormal osteoclast activation through the DUSP4-MAPK signaling axis. Parasitic infection suppresses DUSP4 expression, relieving its negative regulation of the MAPK pathway and leading to excessive osteoclast differentiation. Restoring DUSP4 expression effectively reverses abnormal MAPK pathway activation, reducing osteoclast bone resorption activity to physiological levels. These findings not only provide new insights into the pathological mechanisms of bone destruction in osseous echinococcosis but also establish DUSP4 as a critical therapeutic target for pathological bone resorption, laying the groundwork for host-directed treatment strategies for parasitic bone diseases.